2022
DOI: 10.1108/ijse-06-2021-0351
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution trajectories and life expectancy in Nigeria

Abstract: PurposeThe purpose of the study is to examine the relationship between air pollution and life expectancy considering the roles of institutional quality, agricultural output, foreign direct investment (FDI) and other socio-economic variables in Nigeria from 1981Q1 to 2019Q4.Design/methodology/approachThe study employed spliced quarterly data from annual series collected from the World Bank development indicators and Central Bank of Nigeria. The dynamic multivariate models were analysed using the vector error co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…With the rapid increase in production and consumption of fossil fuel, the emission output continues to depreciate the life and health of nations. In West Africa [ 51 ], investigated Nigeria's air pollution and life expectancy for the quarters 1981Q1 – 2019Q4. The research employed different econometric models and the granger causality test.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rapid increase in production and consumption of fossil fuel, the emission output continues to depreciate the life and health of nations. In West Africa [ 51 ], investigated Nigeria's air pollution and life expectancy for the quarters 1981Q1 – 2019Q4. The research employed different econometric models and the granger causality test.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings revealed that government costs on health and air pollution have a negative impact on human health. By using VECM method, Nwani (2022) displayed that there is a negative relationship between carbon emissions and life expectancy in Nigeria from 1981 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, it was recommended that public education and keeping to international treaties should be prioritized for improved livelihood. Similarly, Nwani 18 evaluated the consequences of air pollution on human health and its sustainability and submitted that, in order to enhance life expectancy in Nigeria, the government should adopt stringent strategies and education to subdue air pollution in the country. Also, Okumagba 19 discovered the poor attitude of the Nigerian government in complying with the court orders and ruling in matters relating to climate litigation (which has been majorly attributed to anthropogenic activities) and, even the weakness of the legal institutions to give such rulings, may jeopardize sustainable environment in the country.…”
Section: Introductionmentioning
confidence: 99%